EFFECTS OF RECREATIONAL TENNIS PRACTICES ON BODY COMPOSITION, FREE TIME MANAGEMENT AND MOTIVATIONAL PERSISTENCE - Tolga Beşikçi,; Nurten Dinç,; İlker Balıkçı,; Ezgi Abay Beşikçi, (PEOPLE: International Journal of Social Sciences, 2025)
This study was conducted to examine the body composition, free time management and motivational persistence of individuals participating in recreational tennis. The sample of the study consisted of administrative staff working at Manisa Celal Bayar University, who voluntarily participated in the study and had never received tennis training before. In the study, pre-test-post-test control group experimental design, one of the quantitative research designs, was used. The experimental study was carried out by forming a study group with a total of 24 personnel (equal number of men and women), 12 of whom were in the control group and 12 in the experimental group. As measurement tools, body composition (data such as body weight, body fat ratios, lean muscle mass and body mass index) were taken with Tanita MC 780 MA brand device. The free time management scale and motivational persistence scale were used as measurement tools. Due to the small number of participants, Mann-Whitney U test, one of the nonparametric tests, was used to observe the differences between the control and experimental groups, and Wilcoxon sequential test was used to analyse the in-group pre-test and post-test data. The relationship between the scales was tested with the ‘Spearman's Correlations’ test. Regarding body composition, it was determined that recreational tennis practices contributed positively to the general health status of the participants. Comparisons between pre- and post-test measurements revealed that the participants showed a significant improvement in using their free time more efficiently as a result of recreational tennis activities. In terms of motivational persistence, it was observed that tennis practices strengthened the participants' determination to achieve their goals. The results of the study show that recreational tennis practices are an important tool that enables individuals to focus on long-term goals and to be resilient against the difficulties they face.